Analisis Semiotika pada Music Video Jkt 48 dengan Judul Benang Sari, Putik dan Kupu-Kupu Malam - Sari, Sri Indah; Ananda, Rizki Ayu; Sazali, Hasan; Dalimunthe, Maulana Andinata (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research focuses on semiotic analysis of music videos which are the pros and cons in society. The music video for JKT 48 is entitled